TUGAS PERBANTUAN TNI DALAM PENANGANAN TERORISME (MILITARY ASSITANCE IN COUNTER-TERRORISM) - Aulia Fitri Rosadi (Jurnal Politica, 2018)
The Indonesian government ratified the revision of the Terrorism Criminal Act which one of the articles regulates the involvement of TNI through the military assistance task in counter terrorism. Furthermore, the regulation regarding the technical involvement of TNI through military assistance will be regulated in a Presidential Regulation, which will be issued a maximum of one year after the ratification of the revised Law on Terrorism. The involvement of the TNI in counter terrorism has triggered public concerns about the possibility of a shift in the mechanism to handle terrorism in Indonesia from criminal justice models that promote law enforcement, to war models that promote the mobilization of military capacity. Even though in practice, the involvement of the TNI was made possible through Military Operations Other Than War. However, Indonesia does not have technical arrangements regarding the mechanism of military assistance. This paper discusses the scheme of involving TNI in counter terrorism within the framework of Military Operation Other Than War with criminal justice model approach, including important points that need to be regulated in the Presidential Regulation concerning military assistance in counter terrorism. AbstrakPemerintah Indonesia mengesahkan revisi Undang-Undang Tindak Pidana Terorisme yang salah satu pasalnya mengatur mengenai pelibatan TNI melalui tugas perbantuan dalam penanganan terorisme. Lebih jauh, pengaturan mengenai teknis pelibatan TNI melalui tugas perbantuan akan diatur dalam Peraturan Presiden (Perpres) yang akan diterbitkan maksimal satu tahun setelah pengesahan revisi Undang-Undang Tindak Pidana Terorisme. Pelibatan TNI dalam penanganan terorisme telah memicu kekhawatiran publik akan kemungkinan terjadinya pergeseran mekanisme penanganan terorisme di Indonesia dari criminal justice model yang mengedepankan penegakan hukum, ke war model yang mengedepankan pengerahan kapasitas militer. Walaupun pada prakteknya, pelibatan TNI dimungkinkan melalui Operasi Militer Selain Perang. Namun, Indonesia belum memiliki pengaturan teknis mengenai mekanisme tugas perbantuan militer. Tulisan ini membahas mengenai skema pelibatan TNI dalam penanganan terorisme dalam kerangka OMSP dengan pendekatan criminal justice model, termasuk hal-hal apa saja yang penting untuk diatur dalam Perpres mengenai perbantuan TNI dalam penanganan terorisme.